Media Discourse Analysis on Deforestation from the Perspective of Sustainable Development in Indonesia - Haris Adri; Eko Priyo Purnomo; Moch. Rifqi Mei Redha; Tiara Khairunnisa (Ikatan Sarjana Komunikasi Indonesia, 2026)
Recurring floods on the island of Sumatra highlight the complex interaction between deforestation, climate change, and environmental governance; however, this relationship is often inadequately represented in media discourse. This study aims to analyze how national and international media frame deforestation and flooding issues from a sustainable development perspective.This research employs a qualitative case study approach, drawing on Norman Fairclough’s Critical Discourse Analysis (CDA), which conceptualizes discourse as a social practice that reflects power relations and ideology. Data were collected from 30 national and international news articles published in 2025 using the NCapture feature and analyzed with NVivo 12 Plus. The analysis focuses on lexical patterns, actor representation, and the construction of relationships between deforestation, climate change, and responsibility distribution. The findings reveal significant differences in media framing. National media tend to emphasize extreme weather and disaster impacts, while international media consistently link flooding to deforestation and ecosystem degradation. These patterns indicate that media discourse can either naturalize environmental disasters or expose their structural causes. This study contributes theoretically by integrating Critical Discourse Analysis with Sustainable Development Goals (SDG 13: Climate Action and SDG 15: Life on Land), offering a novel analytical framework to understand how media discourse shapes environmental accountability and sustainable development narratives in Indonesia.